Endometriosis. Case report - Olga V. Chechulina; Olga V. Danilova (IP Berlin A.V., 2021)
Extragenital endometriosis (EGE) is the rarest variant of endometrioid disease. This is a process in which a benign growth of tissue similar to the endometrium in morphological and functional properties occurs outside the uterine cavity. The manifestation of the disease has an erased course characteristic of other diseases and patients are more likely to end up in non-core departments, which is accompanied by errors in treatment tactics. According to the data of T.V. Dresvyanskaya et al., the frequency of EGE is 68% of the number of all cases of detection of endometrioid disease. The article presents a case of successful surgical treatment of EGE of rare localization.